Development and validation of a UHPLC-ESI-MS/MS method for the quantification of artepillin C in Brazilian green propolis - Lorena Rodrigues Riani; LÍVIA MARA SILVA; OHANA OLIVEIRA ZUZA DA SILVA; LAURIENE RICARDO JUNQUEIRA; JORGE WILLIAN LEANDRO NASCIMENTO; ADEMAR ALVES DA SILVA FILHO (São Paulo State University (UNESP), 2021)
Objectives: The aim of this study was the development and validation of a fast method to quantify artepillin C in green propolis using ultra high-performance liquid chromatography-electrospray ionization-tandem mass spectrometry (UHPLC-ESI-MS/MS). Methods: High purity (97.8%) artepillin C was isolated from green propolis using chromatography techniques. Quantification was performed using a C18(2.1 x 100 mm; 1.7 μm) column, gradient of water and methanol (with 0.01% formic acid) as mobile phase, at a flow rate of 0.4 mL/min and 45 ºC in temperature. A mass spectrometer operated in selected reaction monitoring mode to monitor the deprotonated molecular ion of artepillin C (m/z 299) > fragment ion (m/z 200.12). Several parameters such as specificity, linearity, limit of detection (LOD), limit of quantitation (LOQ), precision, accuracy, and robustness were determined. Results: The method was linear in the 50 - 400 μg/mL range (r2 = 0.9906), showing LOD = 10.79 μg/mL and LOQ = 32.70 μg/mL with satisfactory intra-day and inter-day precision with relative standard deviation (RSD %) of 1.9% and 3.4%, respectively. The accuracy showed recovery of 93-104%, the method was robust and artepillin C was quantified in green propolis at 6.51%. Conclusions: The proposed method showed advantages in comparison with other methods, such as short analysis time and high selectivity for artepillin C.